2016
DOI: 10.1016/j.jtho.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics of RET Rearranged Lung Cancer in European Patients

Abstract: Patients with RET rearranged adenocarcinomas represent a rare and heterogeneous NSCLC subgroup. In some contrast to published data, we see a high prevalence of current and former smokers in our white RET cohort. The significance of co-occurring aberrations, so far, is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…A patient with metastatic PTC experienced durable stable disease following surgical excision of a cutaneous manifestation harboring a CCDC6‐RET fusion and vandetanib treatment . Additionally, partial responses have been reported in patients with RET ‐rearranged NSCLC treated with cabozantinib . Preclinical studies demonstrated that cells transformed by KIF5B ‐ RET are sensitive to treatment with vandetanib, sorafenib, and sunitinib .…”
Section: Discussionmentioning
confidence: 99%
“…A patient with metastatic PTC experienced durable stable disease following surgical excision of a cutaneous manifestation harboring a CCDC6‐RET fusion and vandetanib treatment . Additionally, partial responses have been reported in patients with RET ‐rearranged NSCLC treated with cabozantinib . Preclinical studies demonstrated that cells transformed by KIF5B ‐ RET are sensitive to treatment with vandetanib, sorafenib, and sunitinib .…”
Section: Discussionmentioning
confidence: 99%
“…29,33 ALK, ROS1, and RET were tested for rearrangement by break-apart FISH. 34,35 FISH was performed according to local screening algorithms: FGFR1 screening was performed for squamous cell carcinoma (SqCC) routinely. Starting in June 2014, MET amplification was determined in all patients with the adenocarcinoma (ADC) subtype of NSCLC.…”
Section: Fishmentioning
confidence: 99%
“…9 These are found in 1–2% of unselected lung cancers and tend to be mutually exclusive with other lung cancer drivers. 3 Patients with RET -rearranged lung cancers are commonly never smokers or have a minimal history of prior tobacco exposure.…”
Section: Introductionmentioning
confidence: 99%